From design to reflection: Effects of peer-scoring and comments on students' behavioral patterns and learning outcomes in musical theater performance. (June 2020) - Chen, I-Ching; Hwang, Gwo-Jen; Lai, Chiu-Lin; Wang, Wei-Chun
Abstract: Peer assessment has been regarded as an effective strategy that encourages students to compare and make reflections by reviewing peers' work. Many studies have indicated that students' learning performance improved as a result of integrating the peer assessment mode. Some researchers have been interested in what students do and what they say during peer assessment, and others have also been concerned about the correlation between the qualitative content and students' learning performance. The aim of this study was to investigate students' peer assessment behaviors, and the relationship between their behaviors and their learning performance. Therefore, an online peer assessment learning platform was developed and integrated into a musical theater course in a university in Taiwan. There were three peer assessment modes, namely peer scoring, peer commenting, and peer scoring and commenting. Three classes of students each used one of the three different peer assessment modes. The experimental results showed that the students who learned with the peer scoring and commenting mode improved their musical theater performance; in addition, they provided more critical feedback and performed more behaviors of reading the rubrics, watching example videos, watching peers' work, and reading peers' feedback. Students who learned with the peer scoring mode performed more repeated behaviors of evaluating peers' works, but few behaviors related to viewing others' comments or reading the rubrics were found. Lastly, the students who learned with the peer commenting mode did not perform better compared with those who learned with the other two modes. However, their learning motivation was the highest, and they performed more behaviors of viewing peers' feedback and peers' works. This indicates that the students who learned with the peer commenting mode focused more on the feedback provided by their peers. To sum up, the integrated peer assessment mode that guided students to score and provide comments was an effective learning approach that improved their musical theater skills and led them to perform more complex behaviors than the other two peer assessment modes (i.e., peer scoring or peer commenting). The major contribution of the present study is to perceive peer assessment from the perspectives of both performance and behaviors. Moreover, the findings can be generalized to other courses that engage students in similar forms of assessment where they are viewing videos of each other's practical performance. Highlights: An online peer assessment platform was developed for a musical theater course. The students' learning performance and peer assessment behaviors were investigated. The peer scoring and commenting mode can improve students' musical theater skills. Students who learned with peer scoring and commenting performed complex behaviors. Students who learned with peer scoring and commenting gave more critical feedback.